Circular RNAs as biomarkers and therapeutic targets in cancer. (August 2022) - Beilerli, Aferin; Gareev, Ilgiz; Beylerli, Ozal; Yang, Guang; Pavlov, Valentin; Aliev, Gjumrakch; Ahmad, Aamir
Highlights: Previously thought to be "mistakes" in RNA splicing, the importance of circrNAs is beginning to be appreciated. circRNAs are potential cancer biomarkers. circRNAs are stable and effective miRNA inhibitors. Diagnostic and therapeutic strategies involving circRNAs may be the future of cancer therapy. Abstract: Circular RNAs (circRNAs) are a class of single-stranded closed non-coding RNA molecules (ncRNAs), which are formed as a result of reverse splicing of mRNAs. Despite their relative abundance, an interest in understanding their regulatory importance is rather recent. High stability, abundance and evolutionary conservation among species underline some of their important traits. CircRNAs perform a variety of cellular functions ranging from miRNA and proteins sponges to transcriptional modulation and splicing. Additionally, most circRNAs are expressed aberrantly in pathological conditions suggesting their possible exploitation as diagnostic biomarkers. Their covalent closed cyclic structure resulting in resistance to RNases further makes them suitable as cancer biomarkers. Studies involving human tumors have verified differences in the expression profiles of circRNAs, indicating a regulatory role in cancer pathogenesis and metastasis. As endogenous competitive RNA, circRNAs can regulate tumor proliferation and invasion. Further, some circRNAs located in the nucleus can regulate transcription of genes by binding to RNA polymerase II. In this review, we elaborate the characteristics, functions and mechanisms of action of circRNAs in cancer. We also discuss the possibility of using circRNAs as potential therapeutic targets and biomarkers for cancer.